Discovery of TAK-659 an orally available investigational inhibitor of Spleen Tyrosine Kinase (SYK). Issue 24 (15th December 2016) - Lam, Betty; Arikawa, Yasuyoshi; Cramlett, Joshua; Dong, Qing; de Jong, Ron; Feher, Victoria; Grimshaw, Charles E.; Farrell, Pamela J.; Hoffman, Isaac D.; Jennings, Andy; Jones, Benjamin; Matuszkiewicz, Jennifer; et al.
Graphical abstract: Abstract: Spleen Tyrosine Kinase (SYK) is a non-receptor cytoplasmic tyrosine kinase that is primarily expressed in hematopoietic cells. SYK is a key mediator for a variety of inflammatory cells, including B cells, mast cells, macrophages and neutrophils and therefore, an attractive approach for treatment of both inflammatory diseases and oncology indications. Using in house co-crystal structure information, and structure-based drug design, we designed and optimized a novel series of heteroaromatic pyrrolidinone SYK inhibitors resulting in the selection of the development candidateTAK-659 .TAK-659 is currently undergoing Phase I clinical trials for advanced solid tumor and lymphoma malignancies, a Phase Ib study in advanced solid tumors in combination with nivolumab, and PhIb/II trials for relapsed/refractory AML.